Effects of algae proliferation and density current on the vertical distribution of odor compounds in drinking water reservoirs in summer - Wu, Tianhao; Zhu, Guangwei; Zhu, Mengyuan; Xu, Hai; Yang, Jun; Zhao, Xianfu (Environmental pollution (1987), 2021)
Reservoirs are an important type of drinking water source for megacities, while lots of reservoirs are threatened by odor problems during certain seasons. The influencing factors of odor compounds in reservoirs are still unclear. During August 2019, a nationwide survey investigating the distribution of odor compounds in reservoirs used as drinking water sources was conducted on seven reservoirs. 2-methylisoborneol (2-MIB) and geosmin were detected in almost every reservoir, and some odor compound concentrations even exceeded the odor threshold concentration. The average concentration of 2-MIB was 2.68 ng/L, and geosmin was 3.63 ng/L. The average chlorophyll a concentration was 8.25 μg/L. The dominant genera of phytoplankton in these reservoirs belonged to cyanobacteria and diatom. Statistical analysis showed that odor compound concentration was significantly related to the chlorophyll a concentration and indicated that the odor compounds mainly came from phytoplankton. The concentration of odor compounds in the euphotic zone was significantly related to phytoplankton species and biomass. Therefore, the odor compound concentrations in the subsurface chlorophyll maxima layer was generally higher than in the surface layer. However, the odor compounds in the hypolimnion layer were related to the density current. This research suggests that both phytoplankton proliferation events and heavy storm events are important risk factors increasing odor compounds in reservoirs. Control of algal bloom, in-situ profile monitoring system and depth-adjustable pumping system will greatly reduce the risk of odor problems in reservoirs using as water supplies for large cities. [Display omitted] •Density current may bring lots of odor compounds to deep layer of reservoirs.•Four possible mechanisms that odor problem caused by density current are proposed.•Phytoplankton in SCM layer may produce lots of odor compounds.•Vertical adjustable water intake equipment helps water plants avoid odor problem.